Genome-wide meta-analysis identifies genetic locus on chromosome 9 associated with Modic changes. Issue 7 (26th February 2019) - Freidin, Maxim; Kraatari, Minna; Skarp, Sini; Määttä, Juhani; Kettunen, Johannes; Niinimäki, Jaakko; Karppinen, Jaro; Williams, Frances; Männikkö, Minna
Abstract : Background: Low back pain (LBP) is a common disabling condition. Lumbar disc degeneration (LDD) may be a contributing factor for LBP. Modic change (MC), a distinct phenotype of LDD, is presented as a pathological bone marrow signal change adjacent to vertebral endplate on MRI. It is strongly associated with LBP and has heritability around 30%. Our objective was to identify genetic loci associated with MC using a genome-wide meta-analysis. Methods: Presence of MC was evaluated in lumbar MRI in the Northern Finland Birth Cohort 1966 (n=1182) and TwinsUK (n=647). Genome-wide association analyses were carried out using linear regression model. Inverse-variance weighting approach was used in the meta-analysis. Results: A locus associated with MC (p<5e-8) was found on chromosome 9 with the lead SNP rs1934268 in an intron of the PTPRD gene. It is located in the binding region of BCL11A, SPI1 and PBX3 transcription factors. The SNP was nominally associated with LBP in TwinsUK (p=0.001) but not associated in the UK Biobank (p=0.914). Suggestive signals (p<1e-5) were identified near XKR4, SCIN, MGMT, DLG2, ZNF184 and OPRK1 . Conclusion: PTPRD is a novel candidate gene for MC that may act via the development of cartilage or nervous system; further work is needed to define the mechanisms underlying the pathways leading to development of MC. This is the first genome-wide meta-analysis of MC, and the results pave the way for further studies on the genetic factors underlying the various features of spine degeneration and LBP.